Modeling indices using partial least squares: How to determine the optimum weights? - DİRSEHAN, TAŞKIN (My University, 2022)
© 2022, The Author(s).Indices are often used to model theoretical concepts in economics and finance. Beyond the econometric models used to test the relationships between these variables, partial least squares path modeling (PLS-PM) allows the study of complex models, but it is an estimator that is still in its infancy in economics and finance research. Thus, the use of PLS-PM for composite analysis needs to be explored further. As one such attempt, this paper is focused on the determination of the indices’ optimum weights. For this purpose, the effects of the market potential index (MPI) on foreign direct investment (FDI) and gross domestic product (GDP) were analysed by implementing different weighting schemes. The assessment of the model shows that PLS Mode B leads to better model fit.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Social Sciences and Humanities; Sociology; Temel Bilimler (SCI); Sosyal Bilimler (SOC); Matematik; Sosyal Bilimler Genel; İSTATİSTİK & OLASILIK; Natural Sciences (SCI); Social Sciences (SOC); MATHEMATICS; SOCIAL SCIENCES, GENERAL; STATISTICS & PROBABILITY; İstatistik ve Olasılık; Fizik Bilimleri; Genel Sosyal Bilimler; Sosyal Bilimler ve Beşeri Bilimler; Statistics and Probability; Physical Sciences; General Social Sciences; Social Sciences & Humanities; Composite measurement; Indices; Partial least squares path modeling; PLS Mode A; PLS Mode B; Weighting schemes